Global research trends and hotspots in solar power tower technology: A bibliometric review - Zeshan Aslam; Syed Ihtsham Ul-Haq Gilani; Taib Iskandar Mohamad; Kehinde Temitope Alao (BIORE Scientia Academy, 2025)
Solar Power Towers (SPTs), as a forefront division of Concentrated Solar Power (CSP), have become a promising option for green electricity generation. This paper presents a bibliometric study of global research output in SPTs using data retrieved from the Scopus and Web of Science databases for the period between 2015 and 2024. The 860 documents dataset was mapped using bibliometric tools like VOSviewer and Bibliometrix to examine publication trends, prominent authors, leading institutions, high-output countries, and hot topics of research. The findings illustrate a picture of tremendous growth in publications since 2008 with China, the United States, and Spain as the leading contributors. Heliostat field design, thermal energy storage, receiver efficiency, and system-level optimization are some of the leading research themes. Keyword co-occurrence and co-authorship analysis reveal thematic clustering and changing collaboration patterns, with increasing yet still modest international collaboration. This review presents the current shape and intellectual structure of SPT research, giving a glimpse of its evolutionary trajectory. The findings can help researchers, practitioners, and policymakers identify knowledge gaps and plan future research agendas in the field of solar thermal technologies.